2021
DOI: 10.3126/ijasbt.v9i1.35084
|View full text |Cite
|
Sign up to set email alerts
|

Status and Diversity of Terrestrial plants in Ghodaghodi Lake Complex, Nepal

Abstract: Among the Ramsar sites of Nepal, Ghodaghodi Lake Complex (GLC) is a biodiversity hot spot. This study was carried out to assess the status and diversity of terrestrial plants in GLC. Employing purposive sampling, altogether 38 plots were taken along the right hand side of the foot trails around the GLC. Collected data were analyzed using formulas and Important Value Index (IVI) was calculated. A total of 50 terrestrial species from 27 families were recorded, among which 35 were trees, 8 shrubs, and 7 herbs. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Agaricusbisporusand Boletus edulis was the fungus species present around the lake. Ipomea carnea of Ipomea sps was also recorded in the study carried out by Bhandari et al (2021) in Ghodaghodi Lake Complex which is found as aquatic invasive species in our study area too.…”
Section: Major Plant Speciessupporting
confidence: 72%
“…Agaricusbisporusand Boletus edulis was the fungus species present around the lake. Ipomea carnea of Ipomea sps was also recorded in the study carried out by Bhandari et al (2021) in Ghodaghodi Lake Complex which is found as aquatic invasive species in our study area too.…”
Section: Major Plant Speciessupporting
confidence: 72%
“…The herb species were mostly found in open areas and associated with shrubs, trees and climbers in the study area. Bhattarai (2019), Budha-Magar et al (2020) and Bhandari et al (2021) had also documented higher number of herb species in their studies in Nepal. A total of 176 species were recorded in the wild state and 155 species from cultivation state (Ornamental-75 species, Planted-70 species and agriculture-10 spcies) (Table 1).…”
Section: Life Forms and Cultivation Status Of The Floral Speciesmentioning
confidence: 84%
“…Family Fabaceae represented the maximum number of plant species (n = 26), followed by Asteraceae (n = 25), Poaceae (n = 21), Moraceae (n = 16), and Lamiaceae (n = 14) (Table 1). The maximum number of plant species from the family Fabaceae was also observed in different regions of Nepal (Dhami 2008;Pathak and Baniya 2017;Pandey and Ghimire 2020;Bhandari et al 2021). Fabaceae is the 3rd largest plant family in the world, and possesses wide life forms such as trees, shrubs, herbs and climbers (Watson and Dallwitz 1992;Judd et al 1999;Ahmed et al 2016).…”
Section: Family-wise Composition Of the Floral Speciesmentioning
confidence: 96%